Analisis Faktor Internal Dan Faktor Eksternal Untuk Menentukan Strategi Pemasaran Usahasarang Burung Walet UD. Ikhtiar Di Desa Rensing - M. Zamzami Irhamzani (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This study aimed to determine the internal and external factors to determine the marketing strategy of the swallow's nest business in Rensing Village, East Lombok Regency. From the analysis of these factors, the right strategy is formulated to marketing the business. This research is atype of descriptive research is nsing Village, East Lombok Regency. The sample consisted of 30 swallow nest entrepreneurs whose data collection process used a questionnaire. The data analysis method used is descriptive to explain the internal and external factors of the swallow's nest business and secondly uses SWOT analysis to formulate strategies in marketing mix the swallofors nest business. The results of the analysis using SWOT analysis show that the strategy implemented by swallow nest entrepreneurs in Rensing Village, East Lombok Regency is a WO (Weakness Opportunity) strategy, namely a strategy that overcomes W (weaknesses) by optimizing O (opportunities) that exist in swiftlet farming businesses. In this analysis, it is also known as a management strategy, namely a strategy regarding finance and a product development strategy.